The positive significance of government-organized nationwide sports events in the post-epidemic era: The impact on citizens’ psychological well-being, mindfulness level, and social avoidance distress - Jiansheng Li; Haiqing Wang; Danli Chen; Shuo Yu; Peijie Ding; Haoliang Mai; Weilin Su; Tingwei Chen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Based on the nationwide sports event "Health Walk" held in Ji'an City, we divided the subjects into sports participation group and non-sports participation group to investigate the differences between the two groups in social avoidance and distress, psychological well-being, and mindfulness level. We also examined the mediating role of mindfulness and social avoidance and distress in whether to participate in sports activities and psychological well-being. In addition, we investigated citizens' approval of the government and their city, and collected basic information about the subjects. We used a 2 (sports participation, non-sports participation) * 2 (high social avoidance and distress, low social avoidance and distress) * 2 (high mindfulness level, low mindfulness level) mixed design. We measured the subjects using Watson's Social Avoidance and Distress Scale, the short version of Ryff's Psychological Well-Being Questionnaire, the Chinese Short Version of the Five-Dimensional Mindfulness Scale, and general survey questionnaires. SPSS 27.0 and the PROCESS plug-in were used to process and analyze the data through descriptive statistics, independent sample t-tests, correlation analysis and mediation effect tests. The results showed that there were significant differences in social avoidance, distress, and mindfulness levels in whether to participate in sports activities (ps <0.001). Whether to participate in sports activities and psychological well-being were significantly correlated with mindfulness (t = 0.368, p <0.001; t = 0.250, p <0.01), and were significantly correlated with social avoidance and distress (t = -0.307, p <0.001; t = -0.443, p <0.001). Mindfulness and social avoidance fully mediated the influence of sports participation on psychological well-being (ps <0.001). Government nationwide sports events can effectively improve citizens' psychological well-being by increasing participants' mindfulness levels and reducing social avoidance and distress. At the same time, it has positive effects on citizens' approval of government agencies and improvement of physical and mental health, which is conducive to social development. We should encourage relevant departments and organizations in various cities to carry out similar nationwide and group sports activities in an orderly manner to promote people's physical and mental health and accelerate the recovery and development of social relations in the post-epidemic era.